THE JUSTICE OF EDUCATIONAL COSTS IN THE PERSPECTIVE OF ISLAM AND MORAL PHILOSOPHY - Shaleh, Abdul Rahman; Mubarak, Mubarak -; Mulyati, Sri; Hanifa, Muhammad Aqshalfalah (UIN Antasari Banjarmasin, 2025)
Education plays a very important role in advancing and developing the life of the nation. The government's commitment to this is manifested through the Single Tuition (UKT) system as one of the management ways to be able to present information that can support all activities in higher education. This research is intended to repeat further about this matter. Based on the above presentation, the author is interested in analyzing the unit cost of students at the university level, especially PTKIN based on moral philosophy perspective. Is the Single Tuition (UKT) fulfilling fairness principle in moral perspective. This study used a type of descriptive research with the population being a study program at of PTKI. The sample was taken with a total sampling technique involving 51 Study Programs. Data was taken with FGD. Rawls basic theory of Justice used in viewing fairness element on tuition cost. The results of the study show that there are difficulties in assessing the degree of need in each study program. The needs of study programs must be different based on the cluster of knowledge and competency requirements in each study program. As a result, it is difficult to determine the true size of UKT in fulfilling a demand on fairness. But with the contract principle, tuition cost has fairness. The implication is that a common perception is needed to meet the principles of clarity and fairness in determined tuition cost.